Understanding the dark and bright sides of anxiety: A theory of workplace anxiety. - Cheng, Bonnie Hayden; McCarthy, Julie M. (Journal of Applied Psychology, 2018)
Researchers have uncovered inconsistent relations between anxiety and performance. Although the prominent view is a "dark side," where anxiety has a negative relation with performance, a "bright side" of anxiety has also been suggested. We reconcile past findings by presenting a comprehensive multilevel, multiprocess model of workplace anxiety called the theory of workplace anxiety (TWA). This model highlights the processes and conditions through which workplace anxiety may lead to debilitative and facilitative job performance and includes 19 theoretical propositions. Drawing on past theories of anxiety, resource depletion, cognitive-motivational processing, and performance, we uncover the debilitative and facilitative nature of dispositional and situational workplace anxiety by positioning emotional exhaustion, self-regulatory processing, and cognitive interference as distinct contrasting processes underlying the relationship between workplace anxiety and job performance. Extending our theoretical model, we pinpoint motivation, ability, and emotional intelligence as critical conditions that shape when workplace anxiety will debilitate and facilitate job performance. We also identify the unique employee, job, and situational characteristics that serve as antecedents of dispositional and situational workplace anxiety. The TWA offers a nuanced perspective on workplace anxiety and serves as a foundation for future work. (PsycINFO Database Record